Respuesta :
Answer:
Explanation:
Given that:
[tex]mass \ m_ 1 = 11.0 \ kg[/tex]
[tex]mass \ m_2 = 19.0 \ kg[/tex]
[tex]mass \ of \ the \ pulley\ M = 7.90 \ kg[/tex]
[tex]Radius \ of \ the \ pulley = 0.200\ m[/tex]
1) Provided that the mass in [tex]m_2[/tex] is greater than the mass we have in [tex]m_1[/tex], then likewise the tension we have in [tex]T_2[/tex] will be greater than the tension in [tex]T_1[/tex]
Using Newton's second law to mass [tex]m_1[/tex], we have:
[tex]m_2g - T_2 = m_2 a \\ \\ T_1 = m_1 g +m_1 a \\ \\ T_1= m_1 (g+a) --- (1)[/tex]
By using the second law, we have:
[tex]m_2g - T_2 = m_2a \\ \\ T_2 = m_2 (g-a)---(2)[/tex]
For the pulley, let's use the torque equation, so we have:
[tex]T_2 r -T_1 r = I \alpha \\ \\ T_2r -T_1r = \Big ( \dfrac{Mr^2}{2}\Big) \dfrac{a}{r} \\ \\ T_2 -T_1 = \dfrac{Ma}{2} ---- (3)[/tex]
Altogether, from equation (1)(2) and (3), we have:
[tex]m_2(g-a) -m_1 (g+a) = \dfrac{Ma}{2} \\ \\ m_2g -m_2a -m_1g-m_1a = \dfrac{Ma}{2} \\ \\ a = \dfrac{(m_2 -m_1) g}{(m_1 + m_2 + \dfrac{M}{2})} \\ \\ a = \dfrac{(19.0 \ kg - 11.0 \ kg ) ( 9.8 \ m/s^2)}{(19.0 \ kg + 11.0 \ kg + \dfrac{7.90 \ kg }{2} )}[/tex]
[tex]a = 2.31 \ m/s^2[/tex]
Also; from equation (1), the tension in the string is:
[tex]T_1[/tex] = (11.0 kg ) ( 9.8 + 2.31) m/s²
[tex]T_1[/tex] = 133.21 N
[tex]T_1[/tex] ≅ 133 N
From equation (2):
[tex]T_1[/tex] = m_2(g-a)
[tex]T_1[/tex] = (19.0 kg) ( 9.8 - 2.31) m/s²
[tex]T_1[/tex] = 142.31 N
[tex]T_1[/tex] = 142 N